Characterization of IgG autoantibodies to extracellular matrix protein 1 in lichen sclerosus. - Chan, I; Oyama, N; Neill, S; Wojnarowska, F; Black, M; McGrath, J (2004)
Although the precise aetiology of lichen sclerosus is unknown, evidence for an autoimmune basis to the disorder is emerging. Indeed, circulating IgG autoantibodies to the glycoprotein extracellular matrix protein 1 (ECM1) have been demonstrated in the sera of about 75% of affected individuals. To assess this humoral immune response further, immunoblotting was performed using bacterial recombinant proteins spanning different domains of the ECM1 protein. The aim was to identify autoantibody-reactive sites recognized by 90 lichen sclerosus sera. The subclass distribution of anti-ECM1 IgG autoantibodies was also determined in 54 lichen sclerosus sera. Immunoblotting showed that the IgG autoantibodies from lichen sclerosus patients recognize multiple antigenic reactive sites on the ECM1 protein within both the amino terminus (50/90, 55.6%) and the protein loop cysteine-rich repeat domains (54/90, 60%), although few sera (7/90, 7.8%) had antibodies to the carboxyl terminus of ECM1. IgG subclass analysis revealed that the anti-ECM1 autoantibodies belong predominantly to the IgG(2) subclass (48/54, 88.9%), either IgG(2) alone (28/54, 51.9%) or in combination with one or more other IgG subclasses. No correlation was found between the site(s) of the ECM1 epitopes or the anti-ECM1 IgG profile and any specific clinical parameters. Nevertheless, characterization of anti-ECM1 antibodies does provide further insight into humoral immune responses and understanding disease mechanisms in lichen sclerosus.